Calcareous nannofossil biostratigraphy: historical background and application in Cenozoic chronostratigraphy. (23rd May 2017) - Agnini, Claudia; Monechi, Simonetta; Raffi, Isabella
Abstract : Calcareous nannofossils are considered one of the most powerful biostratigraphical tool in marine carbonate sediments especially in open ocean settings. Their origination goes at least as far back as the Triassic (ca. 220 Ma) when they first biomineralized and produced calcite skeletons. Since then, they have evolved rapidly showing widespread biogeographical distributions. Starting from the 1950s, changes in calcareous nannofossil assemblages have been used to date rocks and sediments and a fundamental step was achieved two decades later with the publication of the first comprehensive biostratigraphical schemes. Standardized quantitative counting methods, unambiguous taxonomy as well as highly resolved data sets provide high‐quality biostratigraphical datums which, in turn, result in the precise positioning of calcareous nannofossil biohorizons and in the construction of reliable biostratigraphical frameworks. Here, we use recently published Cenozoic biozonations as a framework to present an overview of the calcareous nannofossil biohorizons which are used in chronostratigraphy to denote Cenozoic Global Standard Stratotype‐section and Point.